Low‐Intensity Pulsed Ultrasound Stimulation for Bone Fractures Healing: A Review. (5th May 2021) - Palanisamy, Poornima; Alam, Monzurul; Li, Shuai; Chow, Simon K. H.; Zheng, Yong‐Ping
Abstract : Low‐intensity pulsed ultrasound (LIPUS) is a developing technology, which has been proven to improve fracture healing process with minimal thermal effects. This noninvasive treatment accelerates bone formation through various molecular, biological, and biomechanical interactions with tissues and cells. Although LIPUS treatment has shown beneficial effects on different bone fracture locations, only very few studies have examined its effects on deeper bones. This study provides an overview on therapeutic ultrasound for fractured bones, possible mechanisms of action, clinical evidences, current limitations, and its future prospects.